Analisis Efisiensi Energi dan Konservasi Energi Sistem Pendingin Ruangan Berdasarkan UI Greenmetric, Studi Kasus Fakultas Teknik Universitas Udayana - Natapathy, Ranga Bayu; Satya Kumara, I Nyoman; Giriantari, I. A. Dwi (Jurnal Sosial Teknologi, 2025)
The participation of universities in the development of Green Buildings through the implementation of the Green Campus program. One of the benchmarks for Green Campus development is the UI GreenMetric ranking. This research examines one of its assessment indicators, the Use of Energy-Efficient Equipment (EC1). This research evaluates the implementation of energy efficiency through stages ranging from data collection on existing conditions, recommendations for feasible energy efficiencies, comparison of existing energy consumption with the recommendations, and analysis of investment costs to determine the payback period.